Development and characterization of potential larvicidal nanoemulsions against Aedes aegypti - Duarte, Jonatas L.; Di Filippo, Leonardo Delello; de Faria Mota Oliveira, Anna Eliza Maciel; Sábio, Rafael Miguel; Marena, Gabriel Davi; Bauab, Tais Maria; Duque, Cristiane; Corbel, Vincent; Chorilli, Marlus (Beilstein Journal of Nanotechnology, 2024)
Plant-based insecticides offer advantages such as negligible residual effects, reduced risks to both humans and the environment, and immunity to resistance issues that plague conventional chemicals. However, the practical use of monoterpenes in insect control has been hampered by challenges including their poor solubility and stability in aqueous environments. In recent years, the application of nanotechnology-based formulations, specifically nanoemulsions, has emerged as a prospective strategy to surmount these obstacles. In this study, we developed and characterized nanoemulsions based on cymene and myrcene and assessed their toxicity both in vitro using human keratinocytes (HaCAT) cells and in an in vivo model involving Galleria mellonella larvae. Additionally, we investigated the insecticidal efficacy of monoterpenes against the mosquito Aedes aegypti, the primary dengue vector, via larval bioassay. Employing a low-energy approach, we successfully generated nanoemulsions. The cymene-based nanoemulsion exhibited a hydrodynamic diameter of approximately 98 nm and a zeta potential of −25 mV. The myrcene-based nanoemulsion displayed a hydrodynamic diameter of 118 nm and a zeta potential of −20 mV. Notably, both nanoemulsions demonstrated stability over 60 days, accompanied by controlled release properties and low toxicity towards HaCAT cells and Galleria mellonella larvae. Moreover, the nanoemulsions exhibited significant lethality against third-instar Aedes aegypti larvae at a concentration of 50 mg/L. In conclusion, the utilization of nanoemulsions encapsulating cymene and myrcene presents a promising avenue for overcoming the limitations associated with poor solubility and stability of monoterpenes. This study sheds light on the potential of the nanoemulsions as effective and environmentally friendly insecticides in the ongoing battle against mosquito-borne diseases.
Keywords: colloidal stability; drug delivery system; hydrophile–lipophile balance; monoterpenes